L'encaix de la narrativa sense ficció de Víctor Labrado en el paradigma de la novel·la històrica valenciana. - ESCANDELL, DARI (Scripta, 2019)
The Valencian writer Víctor Labrado (Sueca, 1956) has emerged as one of the great contemporary references in the field of the non-fiction novel in Catalan, a narrative subgenre that combines the fictional intention with real testimonial speeches. However, can Labrado's capital books -peculiar, idiosyncratic and unusual- be considered also, without subterfuges or hints, historical novels? Broadly speaking: are his Spanish civil war plots grafted with interviews, generous doses of documentary journalism and almost absolute absence of fiction, historical novels? Its techniques and style are no impediment to say so, if we pay attention to the topoi agreed by the specialized critic. In fact, these novels become, in short, a living testimony of our past time: they rescue from oblivion the experiences and adventures of anonymous people, from the most universal particularity, and the Valencian reality of a past century stigmatized by the civil conflict of 1936 and the consequent dictatorship. Is that enough, however, to attribute this label to the rest of his literary works? This paper analyses the techniques, the plots and the concepts of Labrado's essential books to determine what part of his nonfiction novels may or may not be considered historical.